Base Editing in Peanut Using CRISPR/nCas9 - Neelakandan, Anjanasree K.; Subedi, Binita; Traore, Sy M.; Binagwa, Papias; Wright, David A.; He, Guohao (Frontiers in Genome Editing, 2022)
Peanut (Arachis hypogaea L.), an allotetraploid legume of the Fabaceae family, is able to thrive in tropical and subtropical regions and is considered as a promising oil seed crop worldwide. Increasing the content of oleic acid has become one of the major goals in peanut breeding because of health benefits such as reduced blood cholesterol level, antioxidant properties and industrial benefits such as longer shelf life. Genomic sequencing of peanut has provided evidence of homeologous AhFAD2A and AhFAD2B genes encoding Fatty Acid Desaturase2 (FAD2), which are responsible for catalyzing the conversion of monounsaturated oleic acid into polyunsaturated linoleic acid. Research studies demonstrate that mutations resulting in a frameshift or stop codon in an FAD2 gene leads to higher oleic acid content in oil. In this study, two expression vectors, pDW3873 and pDW3876, were constructed using Cas9 fused to different deaminases, which were tested as tools to induce point mutations in the promoter and the coding sequences of peanut AhFAD2 genes. Both constructs harbor the single nuclease null variant, nCas9 D10A, to which the PmCDA1 cytosine deaminase was fused to the C-terminal (pDW3873) while rAPOBEC1 deaminase and an uracil glycosylase inhibitor (UGI) were fused to the N-terminal and the C-terminal respectively (pDW3876). Three gRNAs were cloned independently into both constructs and the functionality and efficiency were tested at three target sites in the AhFAD2 genes. Both constructs displayed base editing activity in which cytosine was replaced by thymine or other bases in the targeted editing window. pDW3873 showed higher efficiency compared to pDW3876 suggesting that the former is a better base editor in peanut. This is an important step forward considering introgression of existing mutations into elite varieties can take up to 15 years making this tool a benefit for peanut breeders, farmers, industry and ultimately for consumers.